Comparative study of stirrup-confined circular concrete-filled steel tubular stub columns under axial loading. (February 2018) - Ding, Fa-xing; Zhu, Jiang; Cheng, ShanShan; Liu, Xuemei
Abstract: This paper presents a comparative study of circular concrete-filled steel tubular stub columns with three different stirrup confinement types: bidirectional stirrups, loop stirrups and orthogonal stirrups. Axial compression tests have been carried out aiming at investigating the effects of the stirrup form and volume-stirrup ratio on the mechanical behavior of the stirrup-confined circular CFT stub columns, and ABAQUS was used to carry out the 3D numerical modelling. Radial stress of the core concrete and the composite action among the steel tube, stirrups and the core concrete have been investigated. It is found that the confinement provided by stirrups on core concrete strongly outperforms that provided by steel tube, steel sections or steel reinforcement. Furthermore, a simplified approach was developed to predict the ultimate bearing capacity of stirrup-confined circular CFT stub columns, which agreed well with the experimental and numerical results. Highlights: Stirrup-confined circular CFT stub columns have been studied. Experimental and numerical methods have been used to analyze the mechanical properties. A practical formula for calculating ultimate bearing capacities is proposed.